Optimal advertising:Adstock and beyond - Driver, John C.; Foxall, Gordon R. (Cranfield School of Management, 1986)
Decision-makers are frequently exhorted to employ `scientific' budgeting techniques based on the marginal logic of formal economic analysis; some have claimed success in this regard. Yet survey data continue to reveal that most managers in practice use various combinations of ad hoc and, at best, quasi-systematic methods of budget determination. This paper examines the theoretical basis of the prescribed marginal approach and argues that it is generally incapable of implementation given unresolved specification problems in the incorporation of measures of cumulative advertising effect and the behavioural definition of the advertising process.